Pengaruh Budaya Organisasi dan Kompetensi Terhadap Kinerja Pegawai dan Stres Kerja sebagai Variabel Intervening pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Provinsi Jambi - Gustio Aprilda; Arna Suryani; Ali Akbar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The study's first objective was to provide a description of the Jambi Province Regional Finance Agency's organizational culture, competence, work stress, and employee performance. Second to dissect the impact of hierarchical culture and skills straightforwardly and by implication on work pressure Third to break down the impact of authoritative culture and capabilities straightforwardly and in a roundabout way on representative execution. Fourth, to examine the impact of workplace stress on worker performance. Fifth to investigate the impact of hierarchical culture and skill through work weight on the exhibition of representatives of the Jambi Commonplace Territorial Money Organization. The information utilized in the review are optional information. Also, in examining utilizing quantitative illustrative strategies and logical apparatuses utilizing way examination strategies, F tests and t tests and coefficients of assurance (R2). The subject of this study is the Jambi Province Office of the Regional Finance Agency. The populace added up to 310 individuals, with examining utilizing the slovin technique bringing about an example of 76 respondents. The consequences of immediate and circuitous exploration on authoritative culture and capability influence both at the same time and somewhat on work pressure. Furthermore, authoritative culture and skills straightforwardly and by implication influence both at the same time and somewhat on representative execution. Through work stress, employee performance is also positively impacted by organizational culture and competence.